1998
DOI: 10.1042/cs0950649
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Na+/Li+ countertransport and Na+/K+–2Cl− co-transport measurement in essential hypertension: useful diagnostic tools or failure? A meta-analysis of 17 years of literature

Abstract: 1.A meta-analysis of 17 years of literature on erythrocyte Na+/Li+ countertransport (NLCT) and Na+/K+ co-transport (COT) measurements in relation to essential hypertension is presented. The analysis aimed to answer two questions: (i) Which clinical or laboratory variables influence NLCT and COT flux values? (ii) How useful are NLCT and COT measurements as a diagnostic aid in essential hypertension?2. Regression analysis was performed on the mean flux values and relevant clinical and laboratory values. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
2
6
0
3
Order By: Relevance
“…Similar to most previous studies, 5 there is much overlap in Na/Li CT parameters (Figure 1), but the effect of thiol alkylation with NEM on K m was the clearest discriminator in the EHT-FH patients. It was unaffected by plasma triglyceride levels.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similar to most previous studies, 5 there is much overlap in Na/Li CT parameters (Figure 1), but the effect of thiol alkylation with NEM on K m was the clearest discriminator in the EHT-FH patients. It was unaffected by plasma triglyceride levels.…”
Section: Discussionsupporting
confidence: 71%
“…It is clear that in the present study the EHT-FH patients with the abnormal Na/Li CT kinetic parameters that were due to the abnormal thiol protein were very poorly discriminated by the single Na/Li CT flux rate assay. A recent meta-analysis of data from the latter assay concluded that the difference assessed by Na/Li CT flux rate between patients with EHT and NCs was weak but observed that kinetic parameters may be more useful, 5 and this is clearly shown in the present study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It was felt that a simple measurement on red blood cells from individuals in at-risk groups might inform clinicians about appropriate therapeutic strategies or lifestyle advice. However, larger studies failed to find a clear correlation [102], suggesting that measurements of red blood cell Na + -K + -2Cl − cotransport rate had no diagnostic value in essential hypertension. We are now in a position to understand why a connection between hypertension and red blood cell NKCC activity might exist.…”
Section: Wnks Cccs and Bpmentioning
confidence: 85%
“…Na/LiCT has a major inherited component, but is also affected by environmental/metabolic factors, notably circulating plasma lipid concentrations [2]. Hence it has not been a clear marker of disease or disease susceptibility and some studies have shown poor discrimination from NC (normal controls) [3,4]. However, the consistent finding of abnormal Na/LiCT in some groups of patients with EH justifies attempts to understand the molecular mechanism for the association with disease.…”
Section: Introductionmentioning
confidence: 96%